Efficacy of fetal hemoglobin inducers in adult transfusion-dependent beta-thalassemia patients: a systematic review and meta-analysis - Naufal, Muhammad Afif; Fauzi, Ahmad; Rengganis, Iris (Medical Journal of Indonesia, 2025)
BACKGROUND Patients with transfusion-dependent beta-thalassemia (TDBT) face risks of iron overload, which also burdens national expenditures in Indonesia. Elevated fetal hemoglobin (HbF) expression is associated with reduced blood transfusion dependency. This study aimed to assess the efficacy and safety profile of HbF inducers as adjuvant therapy for adult patients with TDBT and appraise its feasibility for Indonesian patients. METHODS This study analyzed 7 trials of HbF inducers, such as hydroxyurea, thalidomide, butyrate, and decitabine, in 382 adult participants (mean age >16), including 28 patients with non-TDBT. Outcomes assessed included hemoglobin (Hb) levels, transfusion needs, and adverse events (AEs). Studies were sourced from PubMed, Cochrane, Embase, and individual searches. The standardized mean difference (SMD) was used as the primary effect size. The protocol was registered in PROSPERO (CRD4202454646368). RESULTS High heterogeneity was observed, with HbF inducers associated with a significant decrease in transfusion needs (SMD = −0.88; 95% confidence interval [CI] = −1.37 to −0.26); I2 = 79%, P✗2<0.01). No significant change in Hb levels was found (SMD = 0.11; 95% CI = −0.69 to 0.91; I2 = 90%, P✗2<0.01). The most common AEs were transaminitis and cytopenias, which were tolerable and alleviated upon dose cessation. CONCLUSIONS HbF induction agents can be used as adjuvant therapy for TDBT, considering their cost-effectiveness, efficacy, and safety profiles.